IMPROVING EMPLOYEE PERFORMANCE THROUGH THE USE OF SOCIAL MEDIA AT THE WORKPLACE: MEDIATED BY EMPLOYEE ENGAGEMENT AND JOB SATISFACTION - Lysandra, Cindy Letitia; Noermijati, Noermijati; Kurniawati, Desi Tri (Jurnal Aplikasi Manajemen, 2023)
Employee performance will be more optimal if the employee combines it with social media. Moreover, social media platforms have various applications supporting employee performance, such as Zoom, Google Meetings, Skype, Telegram, and Whatsapp. Social media has fairly high accessibility, is easy to apply, and provides a variety of certain features that can support employees' work. For this reason, this study will examine the effect of social media on employee performance, mediated by employee engagement and job satisfaction. This research was conducted on educational employees at Brawijaya University Malang. Brawijaya University is one university that uses social media for its employees. Furthermore, the research data were analyzed using PLS (Partial Least Square) with the SEM (Structural Equation Model) approach. The sampling technique used is purposive sampling, but in this study, it is not known for a certain number of employees who use social media, so researchers refer to determining the minimum sample size for the SEM model, which is 5-10 times the number of indicators. Based on these considerations, the respondents obtained a total of 122 employees with the status of State Civil Apparatus. The results of the PLS analysis show that social media has no significant effect on employee performance. Nonetheless, employee engagement and job satisfaction perfectly mediate the relationship between social media and employee performance. Based on the results of this study, it can be concluded that social media can improve the performance of educational employees at Brawijaya University Malang through the mediating role of employee engagement and job satisfaction.